Practical Application of 3D Printing for Pharmaceuticals in Hospitals and Pharmacies - Kampanart Huanbutta; Kanokporn Burapapadh; Pornsak Sriamornsak; Tanikan Sangnim (MDPI AG, 2023)
Three-dimensional (3D) printing is an unrivaled technique that uses computer-aided design and programming to create 3D products by stacking materials on a substrate. Today, 3D printing technology is used in the whole drug development process, from preclinical research to clinical trials to frontline medical treatment. From 2009 to 2020, the number of research articles on 3D printing in healthcare applications surged from around 10 to 2000. Three-dimensional printing technology has been applied to several kinds of drug delivery systems, such as oral controlled release systems, micropills, microchips, implants, microneedles, rapid dissolving tablets, and multiphase release dosage forms. Compared with conventional manufacturing methods of pharmaceutical products, 3D printing has many advantages, including high production rates due to the flexible operating systems and high drug loading with the desired precision and accuracy for potent drugs administered in small doses. The cost of production via 3D printing can be decreased by reducing material wastage, and the process can be adapted to multiple classes of pharmaceutically active ingredients, including those with poor solubility. Although several studies have addressed the benefits of 3D printing technology, hospitals and pharmacies have only implemented this process for a small number of practical applications. This article discusses recent 3D printing applications in hospitals and pharmacies for medicinal preparation. The article also covers the potential future applications of 3D printing in pharmaceuticals.